The diverse interaction of metabolism, immune response, and viral pathogens - Kanno, Toshio; Miyako, Keisuke; Endo, Yusuke (Frontiers in Immunology, 2025)
During viral infections, both innate and adaptive immune responses are activated to establish host defense mechanisms. In innate immunity, the STING and MAVS pathways, which recognize viral genomes, play a central role in inducing type I interferons (IFN-I), a group of antiviral cytokines. Concurrently, adaptive immune responses, particularly those mediated by T cells, contribute to viral clearance and the establishment of immune memory through the recognition of viral antigens. Recently, numerous studies have highlighted the impact of alterations in lipid metabolism on host immune cells during viral infections. Because viruses lack the ability to synthesize their own lipid membranes, they rely on host lipid metabolic pathways to support their replication. In addition, IFN-I signaling has been shown to suppress the expression of lipid metabolic genes and promote the generation of antiviral lipids. Furthermore, following viral infection, both innate and adaptive immune cells rewire various metabolic pathways, including lipid metabolism, glycolysis, the tricarboxylic acid cycle, and amino acid metabolism, to mount effective antiviral responses. This review focuses on recent advances in our understanding of lipid metabolic reprogramming during viral infection at both the cellular and systemic levels, and how such metabolic changes shape and regulate immune responses.